Deciding to drive through floodwater: A qualitative analysis through the lived experience, Royal Life Saving Society – Australia & Griffith University - Hamilton, Kyra; Peden, A.; Keech, J.; Hagger, Martin (Life Savers Magazine, 2016)
More than half of unintentional flood-related drowning deaths in Australia are due to driving through floodwater. Currently, there is a critical knowledge gap in understanding why individuals choose to drive through floodwater and the decisions that may lead to such actions. We propose that a more complete understanding of individuals’ decisions to drive through floodwater needs to be considered in the context of the lived experience.